LEGAL STATUS OF LAND RIGHTS OF THE MINING COMPANIES IN CENTRAL SULAWESI - Lanini, Agus; Syafiuddin, Ikhsan; Ali, Agustina; Sulbadana, Sulbadana; Palipadang, Lembang; Artha Perdana, Budi (Tadulako Social Science and Humaniora Journal, 2021)
This study aims to describe and analyze the legal status of mineral mining companies' land in Central Sulawesi, and secondly to explore and/or find alternative concepts in the field of land use adopted by the community in the mining area and its surroundings. To achieve this goal, a sociological/socio legal research method will be used. Document studies are carried out through a search for legal materials; primary, secondary and tertiary to obtain some data, then field data collection was carried out in the form of observations, in-depth interviews and participatory discussions (PRA). The phenomenon of problematic mineral mining occurs in almost every region in Indonesia, including Central Sulawesi. These facts show the importance of this research to be carried out in Central Sulawesi. Mining business is carried out after obtaining a permit from the government, prior to agreement with the party who has land rights, the government has first issued a mining business permit (hereinafter abbreviated as IUP), after the IUP is issued then a settlement with the party who has land rights in order to obtain approval. Land rights are very important in this regard, so the author is of the opinion that in granting mining business permits, comprehensive and effective consultation and deliberation first need to be carried out, involving communities directly affected by mining business activities, so that land rights are guaranteed optimal